Penentuan Nilai Opsi Call Dan Opsi Put Saham Dengan Menggunakan Model Binomial: Sebuah Kajian Teoritis - Bram Hadianto . (Universitas Kristen Maranatha, 2009)
There are many instruments of investment in the capital market. One of instruments is the option. The quotation of the option depends on its underlying asset. If the asset is the stock, the option is called as the stock option. This paper describes how to determine the value of option based on binomial tree model. Both, forward calculation and backward pricing are used to establish the value of option. For the simplicity, the explanation that performed in this paper doesn't include dividend payment.Keywords: binomial model valuation, real world valuation, risk neutral valuation, backward pricing, European option.